Avaliação da concentração de radônio - 222 nas águas subterrâneas e o risco de exposição para a população de Caçapava do Sul - RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This pioneering work verified the concentration in groundwater of the city of Caçapava do Sul, Rio Grande do Sul / RS, whose population is about 45 thousand inhabitants (IBGE / 2018). Since there is knowledge about the factors that affect the presence of this element in groundwater, and this is the cause of several human health problems, this paper proposes to analyze water samples from the region's tubular and groundwater wells in three distinct lithological domains. . The geology of the area comprises biotite granitoids, leucogranitoids and banded granitoids, which form the Caçapava do Sul Granitic Complex. Concentrations were measured using the AphaGUARD equipment (Genitron GmbH). After obtaining the measurements, they were compared with the limits established by the World Health Organization (WHO), whose maximum value is 100Bq / L (100 disintegrations per second per liter) to verify if they present any risk to the population that uses it. Of the various measurements made in tubular and groundwater wells, a high concentration was noted that is related to granite lithology and geological structures.
Keywords: Radônio; Granito; Poços; AlphaGuard; Caçapava do Sul; Radon; Granite; Wells; CNPQ::CIENCIAS EXATAS E DA TERRA